Spatial and temporal changes in reef fish assemblages on disturbed coral reefs, north Pacific coast of Costa Rica - Arias Godínez, Gustavo (2019)
Benthic structure of coral reefs determines the availability of refuges and food sources. Therefore, structural changes caused by natural and anthropogenic disturbances can have negative impacts on reef‐associated communities. During the 1990s, coral reefs from Bahía Culebra were considered among the most diverse ecosystems along the Pacific coast of Costa Rica; however, recently they have undergone severe deterioration as consequence of chronic stressors such as El Niño‐Southern Oscillation and harmful algal blooms. Reef fish populations in this area have also been intensely exploited. This study compared reef fish assemblages during two periods (1995–1996 and 2014–2016), to determine whether they have experienced changes as a result of natural and anthropogenic disturbances. For both periods, benthic composition and reef fish abundance were recorded using underwater visual censuses. Live coral cover (LCC) decreased from 43.09 ± 18.65% in 1995–1996 to 1.25 ± 2.42% in 2014–2016 (U = 36, p < 0.05). Macroalgal cover (%) in 2014–2016 was sixfold higher than mean values reported for the Eastern Tropical Pacific region. Mean (±SD) fish species richness in 1995–1996 (36.67 ± 14.20) was higher than in 2014–2016 (23.00 ± 9.14; U = 20, p < 0.05). Over 40% of reef fish orders observed in 1995–1996 were not detected in the 2014–2016 surveys, including large‐bodied predators. Reduction in abundance of fish predators such as sharks, grunts, and snappers is likely attributed to changes in habitat structure. Herbivorous such as parrotfishes and pufferfishes increased their abundance at sites with low LCC, probably in response to predators decline and increased algal cover. These findings revealed significant degradation and drastic loss of structural complexity in coral reefs from Bahía Culebra, which now are dominated by macroalgae. The large reduction in structural complexity of coral reefs has resulted in the loss of diversity and key ecological roles (e.g., predation and herbivory), thus potentially reducing the resilience of the entire ecosystem.